Road bike cycling and lower back pain - a literature review - Mokot, Wojciech Jan; Kutyła, Katarzyna; Wasiewicz-Ciach, Paulina; Marzec, Marcelina Teresa; Choiński, Maciej; Kuczyński, Piotr; Marszałek, Anna; Wydra-Rojek, Aleksandra; Łakoma, Aleksandra; Marzec, Weronika Zofia (Quality in Sport, 2024)
Introduction and Purpose This literature review endeavors to provide a current synthesis of the available literature regarding the relationship between road bike cycling and lower back pain (LBP). This review focuses on the aspects of bike fitting, riding position, preexisting LBP, cycling injuries and predisposing risk factors among others. Brief Description of the State of Knowledge Road bike cycling is a popular sport considered to be low-impact physically and easy to start with. So goes the proverb - „it’s as easy as riding a bike”. However the truth may be more complicated. There are many positive effects associated with this sport, such as overall health improvement and the ecological impact, and they are generally well-researched. However it is more difficult to find data regarding the dangers. Improper training program, incorrect bike fit or suboptimal riding position are all factors that can lead to lower back pain (LBP) connected with road bike cycling. Previous injuries and spine health should also be taken into account. Summary In consideration of the gathered evidence it is important to consider the above-mentioned interventions to prevent or stop lower back pain (LBP) from emerging. This literature review struggles to provide a starting point for both cyclists and physicians alike who encounter such a problem. The bike fit, adjusting the bike in accordance with the body of the cyclist, analyzing the cycling position and the training program should be principal points to provide for a pain-free road bike cycling. Further research is needed to determine the long-term effects of such actions and their ability to prevent or stop LBP while/after road bike cycling.